UPAYA MENINGKATKAN KESADARAN BELA NEGARA DAN CIVIC COMPETENCE MELALUI MODEL PENGEMBANGAN PENDIDIKAN BERBASIS KEARIFAN LOKAL - Dwiridotjahjono, Jojok; ., Mulyanto; Iryanti, Endang (Global and Policy Journal of International Relations, 2015)
ABSTRACTThe effort to increase nation’s defence awareness and civic competence on pupils could not be done only with a conventional method and content, which tend to be less accommodating and less exploring of the local wisdom values. Based on these facts, innovations of the learning module are needed to cover loopholes and weaknesses of the conventional learning.The goal of this research is to create a learning module of the nation’s defence education based on local wisdoms through a citizen project learning as an effort to increase nation’s defence awareness and civic competence. This is a mixed method research, using both qualitative and quantitative method with “the dominant-less dominant design” pattern.The analysis shows that citizen project learning module gives a positive impact towards the knowledge, attitude and student skill’s improvement in internalizing nation’s defence awareness values and civic competence. The advantage of citizen project learning module is that this model gave a vast space for student to dig all aspects in themselves, whether it is cognitive, affective and psychomotor.Key Words: Learning Module, Local Wisdom, Citizen Project, Nation’s Defence Awareness, Civic CompetenceDOI:https://doi.org/10.33005/jgp.v3i01.1965